2015
DOI: 10.4172/2155-9864.1000293
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation Increased by Advanced Glycated Hemoglobin

Abstract: Introduction: Many studies have provided strong evidence for an association between diabetes complications and an increase in platelet (PLT) reactivity. Though some metabolic abnormalities have been reported as the major causes of this reactivity and malfunction, the precise mechanism has not been fully elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The fact that, in our study, neither T2DM nor HbA1c was associated with higher platelet reactivity ( Supplementary Table S2 ) appears to be discordant with the results of some previous studies [ 20 , 39 , 40 ]. However, these conflicting results could be a consequence of the dependence of platelet reactivity on multiple factors, including glycemic variability [ 40 ] and short-term hyperglycemia [ 41 ], a fact not reflected by HbA1c.…”
Section: Discussionsupporting
confidence: 85%
“…The fact that, in our study, neither T2DM nor HbA1c was associated with higher platelet reactivity ( Supplementary Table S2 ) appears to be discordant with the results of some previous studies [ 20 , 39 , 40 ]. However, these conflicting results could be a consequence of the dependence of platelet reactivity on multiple factors, including glycemic variability [ 40 ] and short-term hyperglycemia [ 41 ], a fact not reflected by HbA1c.…”
Section: Discussionsupporting
confidence: 85%
“…Although this study did not establish a relationship between pathological values of HbA1c and the occurrence of this complication, it can be understood that the endothelial dysfunction caused by high levels of HbA1c and by Advanced glycation end-products would be one of the pathophysiological mechanisms. In the study by Asadifar et al [77], it was shown that high levels of HbA1c also favored aggregability and the platelet activation which would be responsible for the formation of microthrombi and multi visceral attack which can lead HELLP syndrome.…”
Section: Glycated Hemoglobin and Preeclampsia Prognosismentioning
confidence: 99%
“…Although other hormonal, neuronal, and functional factors are chronically affected as well. In the DMAFs subjects, this is due to either the pancreas not producing enough insulin or the cells of the body not responding properly to the insulin produced, [3][4][5][6][7][8][9][10][11] increasing BLEC-dependent disorders eventually. If DMAFs patients are left untreated, collateral damage and side effects of too much glucose lead to many health complications i.e., platelets hyper-and/or hypo-activities, which both are very dangerous progression when chronically prolonged [4][5][6].…”
mentioning
confidence: 99%
“…In the DMAFs subjects, this is due to either the pancreas not producing enough insulin or the cells of the body not responding properly to the insulin produced, [3][4][5][6][7][8][9][10][11] increasing BLEC-dependent disorders eventually. If DMAFs patients are left untreated, collateral damage and side effects of too much glucose lead to many health complications i.e., platelets hyper-and/or hypo-activities, which both are very dangerous progression when chronically prolonged [4][5][6]. Whether a diabetes patient could be clinically supported in such a way that does not need any medicinal/therapeutic management is a big desired wish of any DMAFs, who are suffering from chronic insulin injection, drug usage, obesity discomfort, and an increased morbidity/mortality risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation